2022
DOI: 10.1371/journal.pgph.0001124
|View full text |Cite
|
Sign up to set email alerts
|

Associations of adverse maternal experiences and diabetes on postnatal maternal depression and child social-emotional outcomes in a South African community cohort

Abstract: Previous literature has identified associations between diabetes during pregnancy and postnatal maternal depression. Both maternal conditions are associated with adverse consequences on childhood development. Despite an especially high prevalence of diabetes during pregnancy and maternal postnatal depression in low- and middle-income countries, related research predominates in high-income countries. In a South African cohort with or without diabetes, we investigated associations between adverse maternal experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, to our knowledge, this is the first study to report perinatal maternal depressive symptoms as a moderator in the association between GDM and child autism behaviors. Our findings are in part supported by a study that reported an association of adverse maternal experiences including prior experiences of trauma with postnatal maternal depressive symptoms and child social‐emotional problems, only among mothers with diabetes during pregnancy (Rayport et al, 2022). ASD is estimated to be 40%–80% heritable; however, both genetic and non‐genetic factors can modulate the penetrance of autism risk genes, which results in a highly heterogeneous ASD phenotype (Rylaarsdam & Guemez‐Gamboa, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…However, to our knowledge, this is the first study to report perinatal maternal depressive symptoms as a moderator in the association between GDM and child autism behaviors. Our findings are in part supported by a study that reported an association of adverse maternal experiences including prior experiences of trauma with postnatal maternal depressive symptoms and child social‐emotional problems, only among mothers with diabetes during pregnancy (Rayport et al, 2022). ASD is estimated to be 40%–80% heritable; however, both genetic and non‐genetic factors can modulate the penetrance of autism risk genes, which results in a highly heterogeneous ASD phenotype (Rylaarsdam & Guemez‐Gamboa, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…As well as research using structured tools there are previous studies which examine exposures associated with single features of social communication development in toddlerhood. Multiple factors including less responsive or less effective maternal parenting styles 34 , 35 , greater maternal depression and experience of trauma 36 and a lower quality home environment 37 have been correlated with less favourable social communication development in toddlerhood.…”
Section: Introductionmentioning
confidence: 99%